SPORTS MARKETING : A STRATEGIC PERSPECTIVE - Shank, Matthew D.; Lyberger, Mark R. (Routledge, 2022)
"Sport Marketing: A Strategic Approach is the most authoritative, comprehensive and engaging introduction to sports marketing currently available. It is the only introductory textbook on this subject to adopt a strategic approach, explaining clearly how every element of the marketing process should be designed and managed, from goal-setting and planning to implementation and control. Covering all the key topics in the sports marketing curriculum, including consumer behavior, market research, promotions, products, pricing, sponsorship, business ethics, technology and e-marketing, the book introduces core theory and concepts, explains best practice, and surveys the rapidly-changing, international sports business environment. Every chapter contains extensive real-world case studies and biographies of key industry figures, and challenging review exercises encourage the reader to reflect critically on their own knowledge and professional practice. Now in a fully revised and updated sixth edition, Sports Marketing: A Strategic Perspective includes expanded coverage of social and digital media, analytics, and ethical issues, as well as a greater number of international cases and examples. In a new feature, successful sport marketers reflect on their careers and how they progressed in the sport marketing industry. It is an essential foundation for any sports marketing or sports business course, and an invaluable reference for any sports marketing practitioner looking to improve their professional practice. A companion website offers additional resources for instructors and students, including an instructor's guide, test questions, presentation slides and useful weblinks"--